Rotavirus vaccine and diarrhea mortality: quantifying regional variation in effect size - Fischer Walker, Christa L; Black, Robert E (BMC public health, 2011)
Background Diarrhea mortality remains a leading cause of child death and rotavirus vaccine an effective tool for preventing severe rotavirus diarrhea. New data suggest vaccine efficacy may vary by region. Methods We reviewed published vaccine efficacy trials to estimate a regional-specific effect of vaccine efficacy on severe rotavirus diarrhea and hospitalizations. We assessed the quality of evidence using a standard protocol and conducted meta-analyses where more than 1 data point was available. Results Rotavirus vaccine prevented severe rotavirus episodes in all regions; 81% of episodes in Latin America, 42.7% of episodes in high-mortality Asia, 50% of episodes in sub-Saharan Africa, 88% of episodes low-mortality Asia and North Africa, and 91% of episodes in developed countries. The effect sizes observed for preventing severe rotavirus diarrhea will be used in LiST as the effect size for rotavirus vaccine on rotavirus-specific diarrhea mortality. Conclusions Vaccine trials have not measured the effect of vaccine on diarrhea mortality. The overall quality of the evidence and consistency observed across studies suggests that estimating mortality based on a severe morbidity reduction is highly plausible.